Approaches and Controversies on the Study of Contemporary Fantastic Literature - Caamaño Morúa, Virginia (2014)
This piece specifically approaches some recent proposals for the study of fantasy literature originated by specialized critics, from both America and Europe. These scholars seek to identify the particular characteristics of this type of literature with the purpose of defining it; with some of them demonstrating the necessity of broadening or modifying the viewpoint established by Todorov in 1970. These objectives have resulted an ongoing arduous task, as specialists have not been able to agree even on whether fantasy literature should be regarded as a genre in itself, or studied from other perspectives.